A SHORT NOTE ON CHANGES IN PRE-ASPIRATION IN WOODS CREE - Starks, Donna; Ballard, Elaine (Linguistica Atlantica, 2003)
Woods Cree has five pre-aspirated consonants which occur in coda position. While the coronal segments, ht and Jus, show little evidence of change, there is substantial evidence of weakening amongst the other three pre-aspirated segments. Data based on natural discourse with a small group of Woods Cree speakers show variation in the production of the pre-aspirated segments with hk and hp simplifying in one direction and hO in the other. This paper documents this change in the Woods Cree community of South Indian Lake, Manitoba.